â€œJEMURTISâ€ Jemuran Otomatis Berbasis Mikrokontroller ATMega 2560 Dengan Memanfaatkan Energi Sinar Matahari - ashegaf, farhan taufiqurrahman (Transient: Jurnal Ilmiah Teknik Elektro, 2018)
Indonesia is one of the countries with a tropical climate. Countries with a tropical climate can only have two kinds of seasons only that is dry and rain. The Tropical Climate has different dimensions throughout the year, that is, it can rain down at any time in any project during the dry season. One more color of tropical climate that is separated by the equator. By having the same position, Indonesia gets a constant supply of sunshine throughout the year. Coupled with the existence of rain Throughout the year, then in Indonesia a lot of which have rain forest or dense jungle forest. Because Indonesia is on the equator or equator (imanijasi paragraph) and also occurs between two continents of Asia and the continent of Australia. This gives effect to the pattern of wind direction in Indonesia which is always changing every 6 months that is the wind of west season and east wind. Cause Indonesia only change season 2 times in one year that is rainy season and dry season without winter, autumn or spring. This is what causes Indonesia to become a tropical climate country. Tropical climate also occurs at temperatures between 0-6000 meters above sea level which has an average degree of 26.3 degrees - 22 degrees Celsius.Jemurtis is a portable technology that utilizes solar thermal energy. Using microcontroller ATMega 2560, this tool is able to detect the rainfall to come.In Karsa Cipta will be made rain detector, temperature, and inertia that can be used for areas that have erratic rainfall. It is expected that this tool can be a solution of the problems that often occur and can save time in the process of drying.